Z dziejów francuskiej debaty o kinie stalinowskim - SZCZEPAŃSKI, TADEUSZ (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
From the French debate about Stalinist cinema Through the juxtaposition of texts by Andre Bazin and Georges Sadoul, the author reconstructs a stormy debate on the reception of Soviet cinema from the Stalinist era in 1950s France.